Hogoh Eat application / Nuradilah Abas … [et al.] - Abas, Nuradilah; Mohamad Isa, Nabita Farhana; Khairuddin, Hanif; Mohd Yasin, Zubaydah; Mat Ariffin, Nur Fadillah; Mohd Azmin, Nurul Azhani (Division of Research and Industry Linkages, 2017)
Food is an important tourist attraction and critical tourism resources. Food also has been identified as a key determinant of tourist decision making and satisfaction. Pahang is one of the states in Malaysia that have a variety of traditional and popular dishes. However, the promotion and the information regarding the food tourism in Pahang are very limited. Therefore the ‘Hogoh Eat' app has been developed. The main purpose of creating a ‘Hogoh Eat’ app is to help tourist to find the variety of traditional and significant food of Pahang. This app consists ten types of most popular traditional dishes in Pahang.